Sekuritisasi Ruang Siber di Indonesia: Ketegangan antara Keamanan Negara dan Keamanan Individu dalam Wacana Kebijakan Digital - Muhammad Dewa Ganesha Ichsan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines how cyber security is constructed as a security threat (securitized) within policy discourse in Indonesia, and how the tension between state security and individual (human) security manifests in that construction. Grounded in the Copenhagen School of Securitization Theory and the human security paradigm, the article addresses a normative question that the dominant, state-centric literature has largely left unanswered: whose security is the state actually protecting in cyberspace? The research adopts a qualitative interpretive design, employing document analysis and a discourse-oriented reading of a purposive corpus comprising legal texts (the Electronic Information and Transactions Law and the Personal Data Protection Law), policy documents (the National Cyber Security Strategy), institutional discourse of state cyber authorities, and constitutional jurisprudence. Three patterns emerge. First, cyber threats are framed as existential dangers to national sovereignty and unity, legitimizing extraordinary state measures. Second, the state functions as the dominant referent object of security, while the individual is more often positioned as a source of risk than as a subject to be protected. Third, a partial shift toward the individual as referent object is visible, chiefly through the statutory recognition of personal data protection, yet this shift coexists with the criminalization of expression that constrains individual security. The article argues that the securitization of cyberspace in Indonesia is ambivalent: it simultaneously promises and threatens individual security. Theoretically, it calls for extending securitization analysis to account for the contestation of referent objects; practically, it argues for selective desecuritization and governance that treats citizens as security subjects rather than mere objects of surveillance.